2019
DOI: 10.3390/cells8080924
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-Dependent Stimulation of IL20RA Orchestrates Immune Cell Trafficking through Lymphatic Endothelium in Patients with Crohn’s Disease

Abstract: Crohn’s disease (CD) is a chronic inflammatory condition that can affect different portions of the gastrointestinal tract. Lymphatic drainage was demonstrated to be dysfunctional in CD pathogenesis, ultimately causing the failure of the resolution of intestinal inflammation. To investigate the molecular mechanisms underlying these dysfunctions, we isolated human intestinal lymphatic endothelial cells (HILECs) from surgical specimens of patients undergoing resection for complicated CD (CD HILEC) and from a dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…According to the enriched KEGG and GO pathways, the DEGs were involved in biological processes related to immune response, myocardial growth and development, cardiac conduction, and electrophysiology. The immune response-related genes included ESR1 [ 48 , 49 ], ITLN1 [ 50 , 51 ], AHNAK2 [ 52 , 53 ], FFAR2 [ 54–56 ], IL20RA [ 57 , 58 ], and VEGFC [ 59 , 60 ]. The myocardial growth and development-related genes included ESR1 [ 61 , 62 ], ITLN1 [ 63 , 64 ], EYA2 [ 65 , 66 ], VEGFC [ 67 ], and DCHS2 [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the enriched KEGG and GO pathways, the DEGs were involved in biological processes related to immune response, myocardial growth and development, cardiac conduction, and electrophysiology. The immune response-related genes included ESR1 [ 48 , 49 ], ITLN1 [ 50 , 51 ], AHNAK2 [ 52 , 53 ], FFAR2 [ 54–56 ], IL20RA [ 57 , 58 ], and VEGFC [ 59 , 60 ]. The myocardial growth and development-related genes included ESR1 [ 61 , 62 ], ITLN1 [ 63 , 64 ], EYA2 [ 65 , 66 ], VEGFC [ 67 ], and DCHS2 [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rs8178555 resides in Interleukin 10 Receptor Subunit Beta ( IL10RB ), which has been shown to also contain a common variant that is 2519 bp apart from rs8178555 and is protective against early‐onset Crohn's disease (Moran et al, 2013). Rs1167848 resides in Interleukin 20 Receptor Subunit Alpha ( IL20RA ), which has been shown to be associated with the resolution of chronic inflammation in patients with Crohn's disease (Ungaro et al, 2019). Rs3218256 resides in Interleukin 2 Receptor Subunit Beta ( IL2RB ), which has plausible association with Crohn's disease in the Tunisian population (Bouzid et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The VEGFR3-phosphoinositide 3-kinase (PI3K) signaling pathway is another important regulatory axis in lymphatic vasculature development, and activation of the PI3K-AKT-mammalian target of rapamycin (mTOR) pathway is involved in CD pathogenesis[ 62 ]. The mTOR signaling pathway plays a pivotal role in CD[ 63 ] and a recent study revealed its active involvement in intestinal lymphatic function through effects on leukocyte trafficking in patients with CD[ 64 ]. Additionally, angiopoietin-TIE signaling contributes to whole-body lymphatic vessel development and is important for mesenteric lymphatic development and maintenance[ 65 , 66 ].…”
Section: Rationale For Considering CD As the Intestinal Manifestation...mentioning
confidence: 99%